Acute Respiratory Distress Syndrome After Uterine Artery Embolization. Issue 4 (October 2018) - Nguyen, Dong Bach; How, Jeffrey; Ziegler, Cleve; Madar, Jaclyn
Abstract : INTRODUCTION: Although uterine artery embolization has been established as a less invasive alternative to hysterectomy or myomectomy for the treatment of uterine leiomyomas, it is not devoid of life-threatening complications. CASE: We present the case of a 44-year-old patient who developed a severe systemic inflammatory response and acute respiratory distress syndrome 5 weeks after uterine artery embolization of a large multileiomyomatous uterus. Deterioration of her clinical status prompted an emergency hysterectomy that led to rapid improvement. CONCLUSION: Although fatalities from septicemia after uterine artery embolization have been reported, aseptic inflammatory responses to uterine degeneration can also lead to multiorgan failure. With recent studies refuting uterine size and leiomyoma location as risk factors, further research is needed to help select appropriate uterine artery embolization candidates. Abstract : Systemic inflammatory response and acute respiratory distress syndrome are rare, life-threatening complications after uterine artery embolization for leiomyomas that may require emergency hysterectomy as treatment.